The New Construction of Inheritance in Minangkabau People: Competition and Strategy to Produce Successful Entrepreneurs in Indonesia - Tarigan, Azhari Akmal; Naldo, Jufri (Millati: Journal of Islamic Studies and Humanities, 2022)
The Minangkabau people are one of the dynamic groups of traders in Indonesia. This study follows a Field Study approach, and it aims to reveal the influence of inheritance when it is used as business capital. The study starts by discussing theoretical debates about inheritance in Islam. Then, it is followed by new construction of inheritance within the Minangkabau tribe. The findings of this study indicate that the management of inheritance into business capital in Minangkabau is a new idea that was never carried out in the past. Furthermore, the productive pattern of inheritance is positively correlated with the economic welfare of a family. Finally, the development of businesses built from inheritance can automatically encourage new Muslim entrepreneurs to compete with other entrepreneurs in Indonesia.